2022
DOI: 10.21037/apm-20-2046
|View full text |Cite
|
Sign up to set email alerts
|

Palliative care education in surgery

Abstract: Though incorporating palliative care principles with standard medical and surgical care has been associated with multiple benefits, surgical training devotes far less time to developing skills within the palliative care domains. In this review, we sought to explore the existing literature concerning palliative care education within the context of surgical training. Current studies may be categorized under two major areas:(I) measurement of trainee exposure through needs assessments and (II) implementation of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…There is increasing recognition across medical and surgical specialties, including PM&R, of the need for and value of PC education for resident trainees. 8,9,[18][19][20][21][22][23][24] In neurology, recommendations for enhancing primary PC education for residents have recently been set forth, which include using patient simulations to practice advanced communication skills and structuring opportunities to debrief after challenging clinical scenarios. 18 Given overlapping neurology/PM&R populations, such recommendations may be valuable to consider in PM&R as well.…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing recognition across medical and surgical specialties, including PM&R, of the need for and value of PC education for resident trainees. 8,9,[18][19][20][21][22][23][24] In neurology, recommendations for enhancing primary PC education for residents have recently been set forth, which include using patient simulations to practice advanced communication skills and structuring opportunities to debrief after challenging clinical scenarios. 18 Given overlapping neurology/PM&R populations, such recommendations may be valuable to consider in PM&R as well.…”
Section: Discussionmentioning
confidence: 99%
“…As Ballou and Brasel remark, the Accreditation Council for Graduate Medical Education (ACGME) dictates a minimum number of a variety of procedures that general surgery residents must complete, yet there is no requirement for palliative procedures or palliative conversations (12). A recent review on palliative care education in surgery found that out of several studies assessing palliative care education in surgical trainees, most trainees lacked any formal training in palliative care (13). The few trainees who did have formal training found the quality of the training to be inferior to their training in clinical or technical skills (13).…”
Section: Introductionmentioning
confidence: 99%
“…A recent review on palliative care education in surgery found that out of several studies assessing palliative care education in surgical trainees, most trainees lacked any formal training in palliative care (13). The few trainees who did have formal training found the quality of the training to be inferior to their training in clinical or technical skills (13).…”
Section: Introductionmentioning
confidence: 99%
“…Palliative care interventions, delivered by either the primary team or a specialty PC team, lead to decreased hospital length of stay (LOS), [2][3][4] decreased intensive care unit (ICU) LOS, 2,3 earlier withdrawal of life-sustaining treatments, 2,5 decreased likelihood of invasive treatments, 5 better symptom management, 2,3,5 and increased goal-concordant care. 2,4 Surgeons face numerous barriers when attempting to integrate PC into their practices, including a lack of both formal and informal PC training, [6][7][8][9] lack of mentorship from surgical colleagues formally trained or well versed in PC, 7,9 time constraints, 7,9 and a surgical culture, although changing, which still often prioritizes lifesaving procedures above all else. 8 The lack of reliable prognostication tools for the multi-injured trauma patient remains a major challenge for clinicians as they attempt to provide prognostic information to patients and families.…”
mentioning
confidence: 99%
“…Surgeons face numerous barriers when attempting to integrate PC into their practices, including a lack of both formal and informal PC training, 6–9 lack of mentorship from surgical colleagues formally trained or well versed in PC, 7,9 time constraints, 7,9 and a surgical culture, although changing, which still often prioritizes lifesaving procedures above all else 8 . The lack of reliable prognostication tools for the multi-injured trauma patient remains a major challenge for clinicians as they attempt to provide prognostic information to patients and families.…”
mentioning
confidence: 99%